2016
DOI: 10.1177/0363546516669326
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of an Injury Prevention Program in Preadolescent Female Soccer Athletes

Abstract: Background Anterior cruciate ligament (ACL) injuries are common, and children as young as 10 years of age exhibit movement patterns associated with an ACL injury risk. Prevention programs have been shown to reduce injury rates, but the mechanisms behind these programs are largely unknown. Few studies have investigated biomechanical changes after injury prevention programs in children. Purpose/Hypothesis To investigate the effects of the F-MARC 11+ injury prevention warm-up program on changes to biomechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 45 publications
1
64
1
9
Order By: Relevance
“…Several studies have shown that the 11+ injury prevention programme can induce various positive adaptations in the long term that may potentially contribute to improving or preventing risky movement patterns [ 16 - 22 ]. For example, Daneshjoo et al [ 20 ] reported that, as compared to a control group, an eight-week 11+ programme increased concentric and eccentric hamstring strength in young male professional soccer players, which might reduce the susceptibility of a player to suffering hamstring muscle injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the 11+ injury prevention programme can induce various positive adaptations in the long term that may potentially contribute to improving or preventing risky movement patterns [ 16 - 22 ]. For example, Daneshjoo et al [ 20 ] reported that, as compared to a control group, an eight-week 11+ programme increased concentric and eccentric hamstring strength in young male professional soccer players, which might reduce the susceptibility of a player to suffering hamstring muscle injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis on the efficacy of the 11+ concluded that the use of the F-MARC injury prevention programme can decrease the risk of non-contact injuries among soccer players by 20 to 50% in the long term [ 15 ]. Additionally, the FIFA 11+ has also been shown to produce positive changes in physical fitness [ 16 , 17 ], muscle activity contribution [ 18 ], motor performance [ 19 ], concentric hamstring strength [ 20 ], neuromuscular control [ 21 ], and peak knee valgus moment [ 22 ]; in the long term, all of these factors may potentially contribute to minimizing risky movement patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the program reduced overall injury rates, but it remained unknown if it reduced ACL injuries in particular. 6,40 Many trials analyzed different neuromuscular training programs designed to reduce the risk for ACL tear in handball female players and showed to reduce in the incidence of overall ACL injury, even if the studies are underpowered. 41 The efficacy of prevention programs in decreasing the incidence of ACL tearing was sustained by the results of meta-analyses published by Hewett in 2010 20 , Yoo in 2010 36 , and Sadoghi in 2012.…”
Section: Prevention Programsmentioning
confidence: 99%
“…Musculoskeletal simulations have shed light on movement disorders by, for example, discovering ways to walk that reduce knee loading [1], revealing that children with cerebral palsy exhibit simplified motor control when walking [2], and reproducing eye disorders that cause double vision [3]. Simulations provide insights to increase safety as we push the limits of human performance, whether that is designing exercise equipment for preserving bone density in low gravity [4], designing exoskeletons to reduce back injuries from heavy lifting [5], or assessing the effect of training programs on knee ligament injuries in soccer [6]. Beyond human health and performance, researchers use musculoskeletal simulations to understand how animals move, for example by studying dinosaur locomotion [7] and differences between human and chimpanzee strength [8].…”
Section: Introductionmentioning
confidence: 99%